Tests of QED at LEP energies using e+e− → γγ(γ) and e+e− → ℓ+ℓ−γγ - Dova, María Teresa (1995)
Total and differential cross sections for the process e+e− → γγ(γ), and the total cross section for the process e+e− → γγγ, are measured at energies around 91 GeV using the data collected with the L3 detector from 1991 to 1993. We set lower limits, at 95% CL, on a contact interaction energy scale parameter Λ > 602 GeV, on the mass of an excited electron and on the QED cut-off parameters Λ+ > 149 GeV and Λ_ > 143 GeV. Upper limits are also set o branching fractions of Z decaying into γγ, π° and ηγ of 5.2 × 10−5, 5.2 × 10−5 and 7.6 × 10−5 respectively. The reactions e+e− → ℓ+ℓ−nγ (ℓ = e, μ, τ) are studied using the data collected from 1990 to 1994. The data are consistent with the QED expectations.